Hepatobiliary Platynosomosis in Black-Tufted Marmosets (Callithrix penicillata): A Lethal Threat for Wildlife and Captive Populations - de Macêdo, Isabel Luana; de Sousa, Davi Emanuel Ribeiro; Souza, Antonizete dos Reis; de Toledo Costa, Gabriela Rodrigues; Scalon, Marcela Corrêa; Duarte, Matheus Almeida; Paludo, Giane Regina; Hoppe, Estevam Guilherme Lux [UNESP]; Oliveira, Wilson Junior [UNESP]; de Oliveira Passos, Pedro Henrique; Romano, Alessandro Pecego Martins; de Lima, Eduardo Mauricio Mendes; et al. (Wiley, 2025)
Helminthic infections, particularly those caused by trematodes, pose a significant health risk to both animals and humans. This study investigates hepatobiliary platynosomosis (HP) caused by Platynosomum illiciens in black-tufted marmosets (Callithrix penicillata) in Central Brazil. Data were retrospectively collected from autopsy records at the Laboratory of Veterinary Pathology and Forensics, University of Brasília, from January 2006 to July 2021. Epidemiological, clinical, and pathological information was analyzed, including comparisons between free-ranging and captive marmosets. A total of 1596 nonhuman primate (NHP) death records were examined, with black-tufted marmosets accounting for 75.6% (1206/1595) of autopsies. HP was identified in 10.8% (131/1206) of these cases. Captive marmosets showed a higher prevalence of HP (49.6%) than free-ranging ones (6.5%). This study revealed a significant seasonal trend, with higher HP prevalence observed during the wet season until the onset of the dry season. Pathological examinations revealed severe liver and bile duct damage in fatal HP cases, including fibrosis, bile duct thickening, and the presence of flukes. Captive marmosets exhibited pronounced clinical signs, such as weight loss and apathy. Morphological and molecular analysis of sampled flukes confirmed P. illiciens infecting the marmosets. These findings underscore the substantial impact of HP on marmoset populations, particularly in captive settings. The high lethality (58% overall; 81.6% in captivity) highlights the need for improved management and preventive measures in captive environments. This study contributes to understanding HP epidemiology, clinical manifestations, and pathological outcomes, underscoring the disease's significance for the health of both free-ranging and captive NHP populations. Our findings also support the need to develop targeted strategies to mitigate the impact of HP on primate species populations.
Keywords: flukes; liver; marmoset; Platynosomum illiciens; primates